2022
DOI: 10.1111/mcn.13337
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up and growing‐up formula promotion among Mexican pregnant women and mothers of children under 18 months old

Abstract: Milk formula sales have grown globally, particularly through follow-up formulas (FUF) and growing-up milks (GUM). Marketing strategies and weak regulatory and institutional arrangements are important contributors to caregivers' decisions about child feeding choices. This study describes maternal awareness, beliefs, and normative referents of FUFs and GUMs among Mexican pregnant women and mothers of children 0-18 months (n = 1044) through the lens of the theory of reasoned action (TRA). A cross-sectional survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
(44 reference statements)
0
9
0
3
Order By: Relevance
“…Company’s representants declared that they promote only baby foods and growing-up milk for children from 1 year of age, which they perceive to be outside the scope of the Code. Growing-up milks are increasingly being marketed and recommended by health professionals in Mexico, making women believe their children need these products [ 41 ]. Widening the range of milk formulas for older children have been documented as part of the strategies used by industry to face regulations they perceived as applying only to infant formula and expand their business [ 5 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Company’s representants declared that they promote only baby foods and growing-up milk for children from 1 year of age, which they perceive to be outside the scope of the Code. Growing-up milks are increasingly being marketed and recommended by health professionals in Mexico, making women believe their children need these products [ 41 ]. Widening the range of milk formulas for older children have been documented as part of the strategies used by industry to face regulations they perceived as applying only to infant formula and expand their business [ 5 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors highlight the new BMS promotion strategies such as emergence of new products and marketing practices through social media to circumvent the Code. Two articles in this supplement (Sheikh et al, 2022;Vilar-Compte, Hernández Cordero, et al, 2022) Through a qualitative thematic analysis, guided by the "Breastfeeding Gear Model" (Pérez-Escamilla et al, 2012) the authors systematically documented key enabling factors that facilitated the scaling up of interventions, policies or programmes to promote, protect and support breastfeeding, and how hindering factor was overcome. On one hand, findings showed that each of the four countries followed different processes and timing to implement and scale-up strategies.…”
Section: Key Messagesmentioning
confidence: 99%
“…The authors highlight the new BMS promotion strategies such as emergence of new products and marketing practices through social media to circumvent the Code. Two articles in this supplement (Sheikh et al, 2022; Vilar‐Compte, Hernández Cordero, et al, 2022) describe inappropriate BMS promotion practices in Bangladesh and in Mexico, respectively. Sheikh et al, document, for the first time in Bangladesh, the prevalence of Code violations in small grocery stores, supermarkets or grocery chain stores, baby stores, and also through traditional and social media.…”
mentioning
confidence: 99%
“…As highlighted in the recent report from the World Health Organization (WHO) and United Nations Children’s Fund (UNICEF),1 health systems and health workers have significant influence on decisions and practices related to IYCF and child care. CMF companies understand the influence of health workers on feeding decisions and consequently focus marketing efforts on those responsible for health policies and practices—service managers, health workers and their professional associations, researchers and academic institutions 4–7. Their many and varied marketing tactics include providing financial support to attend conferences, funding conferences, providing education sessions, funding research, donating low-cost supplies of CMF to health services and in emergency situations, donating equipment and providing IYCF ‘education’ to parents via the health system, among others 8–11…”
mentioning
confidence: 99%
“…CMF companies understand the influence of health workers on feeding decisions and consequently focus marketing efforts on those responsible for health policies and practicesservice managers, health workers and their professional associations, researchers and academic institutions. [4][5][6][7] Their many and varied marketing tactics include providing financial support to attend conferences, funding conferences, providing education sessions, funding research, donating lowcost supplies of CMF to health services and in emergency situations, donating equipment and providing IYCF 'education' to parents via the health system, among others. [8][9][10][11] These approaches create conflicts for the health system and health workers influencing them to act in ways that impede fulfilling their ethical obligations, compromise professional judgement, integrity and public credibility towards their protection of breastfeeding, at both individual and institutional levels.…”
mentioning
confidence: 99%